Anodic TiO2 Nanotube Layers for Wastewater and Air Treatments: Assessment of Performance Using Sulfamethoxazole Degradation and N2O Reduction - Sihor, Marcel; Gowrisankaran, Sridhar; Martaus, Alexandr; Motola, Martin; Mailhot, Gilles; Brigante, Marcello; Monfort, Olivier (Molecules (Basel, Switzerland), 2022)
The preparation of anodic TiO2 nanotube layers has been performed using electrochemical anodization of Ti foil for 4 h at different voltages (from 0 V to 80 V). In addition, a TiO2 thin layer has been also prepared using the sol-gel method. All the photocatalysts have been characterized by XRD, SEM, and DRS to investigate the crystalline phase composition, the surface morphology, and the optical properties, respectively. The performance of the photocatalyst has been assessed in versatile photocatalytic reactions including the reduction of N2O gas and the oxidation of aqueous sulfamethoxazole. Due to their high specific surface area and excellent charge carriers transport, anodic TiO2 nanotube layers have exhibited the highest N2O conversion rate (up to 10% after 22 h) and the highest degradation extent of sulfamethoxazole (about 65% after 4 h) under UVA light. The degradation mechanism of sulfamethoxazole has been investigated by analyzing its transformation products by LC-MS and the predominant role of hydroxyl radicals has been confirmed. Finally, the efficiency of the anodic TiO2 nanotube layer has been tested in real wastewater reaching up to 45% of sulfamethoxazole degradation after 4 h.
Keywords: Wastewater; Sulfamethoxazole; photocatalysis; air treatment; nanotrubičky; water treatment; odpadní voda; N2O; Catalysis; Nanotubes; Titanium; TiO2; pharmaceutical; katalýza; titan; sulfamethoxazol